Implementasi Media Wordwall Pada Pembelajaran Syu‘Abul Iman Siswa Kelas X SMA It Unggul Al-Munadi - Pratiwi, Tiara; Zailani, Zailani (Journal of Sustainable Education, 2025)
This study aims to describe the implementation of Wordwall media in improving students’ understanding of Islamic Religious Education concepts, specifically on the topic of syu‘abul iman, in grade X at SMA IT Unggul Almunadi. The background of this research stems from the challenges of PAI learning, which is often considered monotonous, especially in teaching syu‘abul iman with its numerous and abstract branches. The research employed a qualitative case study method. The subjects were grade X students, with data collected through observation, interviews, and documentation, then analyzed descriptively using source triangulation. The findings reveal that Wordwall effectively enhances students’ cognitive, affective, and psychomotor domains. Students were able to understand and classify the branches of faith more easily, showed greater motivation and confidence, and actively participated in class activities. Supporting factors included teacher readiness, students’ digital literacy, and the relevance of media to the material, while barriers involved limited internet, devices, and time. Thus, Wordwall serves as an innovative alternative for creating interactive, enjoyable, and meaningful PAI learning.